Endophytism: A Multidimensional Approach to Plant–Prokaryotic Microbe Interaction - Rani, Simran; Kumar, Pradeep; Dahiya, Priyanka; Maheshwari, Rajat; Dang, Amita Suneja; Suneja, Pooja (Frontiers in Microbiology, 2022)
Plant growth and development is positively regulated by the endophytic microbiome via both direct and indirect perspectives. Endophytes use phytohormone production to promote plant health along with other added benefits such as nutrients acquisition, nitrogen fixation, and survival under abiotic and biotic stress conditions. The ability of endophytes to penetrate the plant tissues, reside and interact with host in multiple ways makes them unique. The common assumption that these endophytes interact with plants in the similar manner as the rhizospheric bacteria is a deterring factor to go deeper into their study, and more focus was on symbiotic associations and plant-pathogen reactions. The current focus has shifted on the complexity of relationships between host plants and their endophytic counterparts. It would be gripping to inspect how endophytes influence host gene expression and can be utilised to climb the ladder of 'Sustainable agriculture'. Advances in various molecular techniques have provided an impetus to elucidate the complexity of endophytic microbiome. The present review is focused on canvassing different aspects concerned with multidimensional interaction of endophytes with plants alongwith their application.